2002
DOI: 10.1007/s00348-002-0429-4
|View full text |Cite
|
Sign up to set email alerts
|

Fully developed laminar flow of non-Newtonian liquids through annuli: comparison of numerical calculations with experiments

Abstract: Experimental data are reported for fully developed laminar flow of a shear-thinning liquid through both a concentric and an 80% eccentric annulus with and without centrebody rotation. The working fluid was an aqueous solution of 0.1% xanthan gum and 0.1% carboxymethylcellulose for which the flow curve is well represented by the Cross model. Comparisons are reported between numerical calculations and the flow data, as well as with other laminar annular-flow data for a variety of shear-thinning liquids previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 28 publications
1
41
0
3
Order By: Relevance
“…In the last 10 years, purely numerical procedures have been used to solve the complete problem of fluid flow and heat transfer of non-Newtonian fluids in concentric and eccentric annular geometries with and without centre-body rotation Escudier, Oliveira, Pinho, & Smith, 2002;Fang, Manglik, & Jog, 1999;Kaneda, Yu, Ozoe, & Churchill, 2003;Manglik & Fang, 2002;Nouar, Benaouda-Zouaoui, & Desaubry, 2000;Soares, Naccache, & Mendes, 2003;Viana, Nascimento, Quaresma, & Macêdo, 2001), which is very interesting from a theoretical point of view, but not easily applicable. On the other hand, few studies report experimental pressure loss and friction factors-Reynolds number data (Escudier, Gouldson, & Jones, 1995;Ilicali & Engez, 1996;Tuoc & Mcgiven, 1994;Vaughn, 1963;Vaughn & Bergman, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, purely numerical procedures have been used to solve the complete problem of fluid flow and heat transfer of non-Newtonian fluids in concentric and eccentric annular geometries with and without centre-body rotation Escudier, Oliveira, Pinho, & Smith, 2002;Fang, Manglik, & Jog, 1999;Kaneda, Yu, Ozoe, & Churchill, 2003;Manglik & Fang, 2002;Nouar, Benaouda-Zouaoui, & Desaubry, 2000;Soares, Naccache, & Mendes, 2003;Viana, Nascimento, Quaresma, & Macêdo, 2001), which is very interesting from a theoretical point of view, but not easily applicable. On the other hand, few studies report experimental pressure loss and friction factors-Reynolds number data (Escudier, Gouldson, & Jones, 1995;Ilicali & Engez, 1996;Tuoc & Mcgiven, 1994;Vaughn, 1963;Vaughn & Bergman, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…For an annular geometry the literature is rich in analytical solutions for the pressure driven case [17][18][19][20][21][22] with applications to the oil and gas industries. For the electro-osmotic flow through an annulus, the applications to real life are becoming important in biological systems as in electrophoretic separation of proteins and for blending chemical and biological fluids [26].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the friction factor increased with decrease in the flow index and he Nusselt number increased with decreasing flow indices (n) and Nusselt number increases with decreasing (n). The flow of non-Newtonian fluid in annulus also studied by [24,25]. Very little work has been done in the experimental study the flow and thermal characterizations together of BMF flows in annular space and cools by nanofluid flows in inner pipe in double-pipe heat exchanger.…”
Section: Introductionmentioning
confidence: 99%